Microsoft Office Professional 2010 step by step - Cox, Joyce, 1946- (Microsoft ; PHI Learning Pvt. Ltd., 2011)
Presents a guide to Office Professional 2010, describing such tasks as creating documents, spreadsheets, and slide presentations, managing email, and organizing notes, covering the Microsoft programs Word, Excel, Access, OneNote, Publisher, Outlook, and PowerPoint.